Increased Screen Use on Days With Increased Perceived COVID-19-Related Confinements—A Day Level Ecological Momentary Assessment Study - Arend, Ann-Kathrin; Blechert, Jens; Pannicke, Björn; Reichenberger, Julia (Frontiers in Public Health, 2021)
Introduction. The coronavirus (COVID-19) quickly evolved into a global pandemic in early 2020 and most countries enforced social confinements to reduce transmission. This seems to dovetail with increasing, potentially problematic, screen use habits like gaming and ‘binge watching’. Yet, the subjective experience of the common confinements may vary not only between individuals, depending on age, sex and living conditions (i.e., living alone) but also within individuals from day to day: confinements might interfere with habitual activity schedules more strongly on some days than on others. Such dynamic confinement experience has not been studied in relation to screen use yet but might guide targeted intervention. Method. In total 102 participants (n = 83 female, n = 80 university students) completed 14 days of ecological momentary assessment during a COVID-19-related lockdown in Germany and Austria. Each evening, they indicated the extent to which they felt restricted by confinements in their social and work life and whether they engaged in unusually high and intense levels of television watching, social media use, news consumption, internet surfing and gaming. They also reported on how much they experienced their day to be structured. Results. Experienced work confinements were positively associated with social media usage. Further, work confinements were positively associated with gaming in males and with news consumption, especially in individuals living alone. Social confinements were positively associated with watching television especially in younger participants and with social media consumption in younger participants. Higher experienced day structure related to less television watching, gaming and internet surfing but more news consumption. Discussion. Screen use behaviors increased with higher confinements within person, dependent on sex, age and living situation. Such knowledge allows tailoring on the person level (who should be addressed?) and the time level (when should interventions be scheduled?) as the negative consequences of excessive screen use behaviors on mental and physical health are well documented. One potential low-threshold intervention might be day-structuring.